The impact of the abuse-deterrent reformulation of extended-release OxyContin on prescription pain reliever misuse and heroin initiation. (June 2020) - Wolff, Carolyn; Dowd, William N.; Ali, Mir M.; McClellan, Chandler; Meinhofer, Angelica; Glos, Lukas; Mutter, Ryan; Rosenberg, Matthew; Schick, Andreas
Highlights: Odds of prescription pain reliever misuse declined with abuse-deterrent OxyContin. Odds of heroin initiation declined with abuse-deterrent OxyContin. No evidence that the odds of heroin use changed due to the OxyContin reformulation. Abstract: The introduction of abuse-deterrent OxyContin in 2010 was intended to reduce its misuse by making it more tamper resistant. However, some studies have suggested that this reformulation might have had unintended consequences, such as increases in heroin-related deaths. We used the 2005–2014 cross-sectional U.S. National Survey on Drug Use and Health to explore the impact of this reformulation on intermediate outcomes that precede heroin-related deaths for individuals with a history of OxyContin misuse. Our study sample consisted of adults who misused any prescription pain reliever prior to the reformulation of OxyContin (n = 81, 400). Those who misused OxyContin prior to the reformulation were considered the exposed group and those who misused other prescription pain relievers prior to the reformulation were considered the unexposed group. We employed multivariate logistic regression under a difference-in-differences framework to examine the effect of the reformulation on five dichotomous outcomes: prescription pain reliever misuse; prescription pain reliever use disorder; heroin use; heroin use disorder; and heroin initiation. We found a net reduction in the odds of prescription pain reliever misuse (OR:0.791, p < 0.001) and heroin initiation (OR:0.422, p = 0.011) after the reformulation for the exposed group relative to the unexposed group. We found no statistically significant effects of the reformulation on prescription pain reliever use disorder (OR: 0.934, p = 0.524), heroin use (OR: 1.014p = 0.941), and heroin use disorder (OR: 1.063, p = 0.804). Thus, the reformulation of OxyContin appears to have reduced prescription pain reliever misuse without contributing to relatively greater new heroin use among those who misused OxyContin prior to the reformulation.